Extracellular MMP-9-Based Assessment of Ocular Surface Inflammation in Patients with Primary Open-Angle Glaucoma - Szaflik, Jacek P.; Wawrzyniak, Zbigniew M.; Strzemecka, Ewa; Zaleska-Żmijewska, Anna (Journal of ophthalmology, 2019)
Purpose. Objective assessment of dry eye disease (DED) severity and ocular inflammation using the InflammaDry® test for extracellular matrix metalloproteinase-9 (MMP-9) and the impact of antiglaucoma eye drops in people with primary open-angle glaucoma (POAG). Methods. Overall, 90 adults (180 eyes) were included: 60 had been diagnosed with POAG and were treated with prostaglandin analogue monotherapy and 30 were suspected of having POAG but did not receive any treatment (control group). Of those treated with prostaglandin eye drops, 30 received a preservative-free formulation (tafluprost) and 30 were treated with a formulation containing the preservative benzalkonium chloride (BAK) (latanoprost). Measurement of extracellular MMP-9 levels (InflammaDry test) provided a marker for ocular surface inflammation. Further assessments of disease severity and inflammation comprised Goldmann applanation tonometry for intraocular pressure (IOP), Schirmer’s test with anesthesia, ocular surface staining with unpreserved fluorescein (Oxford scale index), tear breakup time (TBUT), McMonnies questionnaire, and the Ocular Surface Disease index (OSDI). Results. Clinically significant MMP-9 levels (>40 ng/mL) were detected in tear film from 46.7% of subjects treated with BAK-containing medication. In contrast, only 16.7% of subjects treated with preservative-free medication or untreated individuals demonstrated similar MMP-9 levels. This difference was statistically significant (p<0.05). MMP-9 results correlated with other indicators of inflammation and disease severity. BAK-containing medication was associated with rapid TBUT (<5 seconds) in 50% of cases, while only 10% of untreated subjects and individuals using preservative-free medication demonstrated comparable TBUT results. Conclusion. Measurement of ocular surface MMP-9 level provides a useful marker for inflammation and DED in POAG. Use of a preservative-free topical prostaglandin formulation results in lower levels of ocular inflammation, compared with BAK-containing medication.